Measuring Anxiety Level of Failure Science Students in Performing Calculus Subject - A. Wahab, J.; F. Mohamad Razi, N.; M. H. Mohammad Hamzah, M.; Z. Azmi, A.; H. Nasrudin, N. (International Journal of Engineering and Technology, 2018)
Nowadays, mathematics has become an important subject in various fields. In UiTM Tapah Campus, Calculus is one of the compulsory subject must be taken by science student. However, majority of the students not enjoyable to enroll this subject and have negative thought that slowly becomes obstacle to them to graduate on time due to failure in this subject. Anxiety has been identified as the main reason among failure students. Thus, a set of questionnaire to measure anxiety level among them been constructed consists of three main section (General Information, Test Anxiety, Mathematics Anxiety) and been distributed through Google form in order to get the response from students. The data have been analyzed using IBM SPSS (V23). Several selection of data analysis method was used to answer the objectives for this study which are reliability test, descriptive statistics and ANOVA. Findings shows that student with lower grade (E or F) tended to have higher math and test anxiety compared to higher grade students (D and D+). Thus, lecturers can focus on the most affected students and give them the most exposure to mathematical activities.Â It also benefits university to achieve university target in Graduate on Time (GoT) studentsâ€™ percentage.Â Â